Countering Educational Poverty by Raising Learning Outcomes of Young People - Zelinka, Jozef; Jablonczay, Nikoletta; Zarifis, Georgios K.; Järvinen, Tero (Bloomsbury Academic, 2026)
The decline in German students’ performance in the PISA study is a cause for great concern. Good education is the most important basis for our prosperity … In math and reading, the performance of 15-year-olds is a whole school year behind where it was just four years ago. This decline in educational results is unprecedented. Performance has even fallen below the level that triggered the first PISA shock about 20 years ago. In this most recent study, German students’ performance in mathematics dropped by 25 PISA points, which will cost Germany around EUR 14 trillion in economic output by the end of the century.
Constructing Learning Outcomes: Problematizing (Under)Achievement in Europe